Analisis Hukum Perbandingan Sistem Outsourcing di Indonesia dan Meksiko - Eva Febriani; Muh. Ali Masnun (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Outsourcing, according to Law No. 13 of 2003 on Manpower, is only permitted in supporting sectors. Following the regulatory changes in Law No. 6 of 2023 in Job Creation, outsourcing opportunities are now open to all sectors. Meanwhile, following the 2021 reform of the Ley Federal del Trabajo, Mexico has impelemented significant improvements to outsourcing regulations by imposing restrictions on employment sectors. This research serves as a basis for evaluation and reccomendations for policymakers to create a fair, balanced and sustainble employment system.